The Impact of Aggregate Uncertainty on Firm-Level Uncertainty - Joshy Easaw; Christian Grimme (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We analyse the extent to which firm-level uncertainty is affected by aggregate uncertainty. Firm-level uncertainty is constructed from a large and monthly panel dataset of manufacturing firms. We find that aggregate uncertainty has a positive and robust impact on firm-level uncertainty. This effect holds across different types of domestic and international measures of aggregate uncertainty. However, the size of the impact is heterogeneous and depends on certain firm characteristics and the state of the business cycle. For example, the widely used economic policy uncertainty index matters to all firms' uncertainty only in recessionary periods, while it is relevant over the entire business cycle only to large firms' uncertainty.
Keywords: C23; E32; E01; 330; firm-level uncertainty; aggregate uncertainty; survey data